(untitled) (UCC Student Medical Journal, 2024)
Background: Borderline Personality Disorder (BPD) is a significant public health concern, affecting an estimated 28,725 individuals in Ireland with considerable associated costs. Despite its complexity, the biopsychosocial model offers a comprehensive approach, enabling clinicians to integrate predisposing, precipitating, perpetuating, and protective factors when understanding and managing BPD. Objective: This report presents a case study of a 35-year-old woman with a background of BPD and substance abuse, detailing her biopsychosocial formulation during an episode of acute suicidal ideation. Methods: The case entailed a thorough history and clinical examination, focusing on the biopsychosocial model’s 4P causal framework: predisposing, precipitating, perpetuating, and protective factors. Results: Predisposing factors were abundant, including family history of mental health disorders and personal history of trauma. Precipitating factors were multi-faceted, encompassing biological vulnerabilities from alcohol abuse and significant recent social stressors, such as unemployment, eviction, custody battles, and bereavement. Perpetuating elements revolved around ongoing legal challenges and deep-seated feelings of guilt. However, protective factors were also present: no co-existing medical conditions, an eventual stable mood post-treatment, and engagement in therapeutic activities, including mindfulness interventions. Conclusion: This case underscores the value of the biopsychosocial model in psychiatric patient care, highlighting its potential to uncover individualized nuances in classic presentations. Embracing this model can optimize holistic care, underscoring its imperative utility in clinical practice.